2007
DOI: 10.1200/jco.2007.25.18_suppl.1102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of bone metastasis (BM) growth in patients with metastatic breast cancer (MBC): An exploratory study

Abstract: 1102 Background: The benefits of bisphosphonates (BPs) in reducing or delaying skeletal related events (SREs) in patients with BM have been attributed to their potent osteoclast (OC) inhibiting effect. However, despite the use of modern systemic anti-cancer therapy including potent BPs, many patients with BM continue to suffer from the consequences of their bone disease. An improved understanding of the basic mechanisms of bone destruction would allow further appropriate targeted treatment strategies to be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therapeutic Advances in Medical Oncology 2 (2) levels following sunitinib treatment and bone tumor growth was stunted as evidenced by bioluminescence imaging. While VEGF has been demonstrated to be over-expressed in actual bone metastases from breast cancer patients [Ooi et al 2007], this does not seem to be a prominent feature of RCC bone metastases. In fact, one series of 20 cases showed that VEGFR-2 protein expression fell from 35% in the primary specimen to 10% in the bone metastases suggesting a phenotypic change during progression to the bones [Badalian et al 2007].…”
Section: Trial Limitationsmentioning
confidence: 99%
“…Therapeutic Advances in Medical Oncology 2 (2) levels following sunitinib treatment and bone tumor growth was stunted as evidenced by bioluminescence imaging. While VEGF has been demonstrated to be over-expressed in actual bone metastases from breast cancer patients [Ooi et al 2007], this does not seem to be a prominent feature of RCC bone metastases. In fact, one series of 20 cases showed that VEGFR-2 protein expression fell from 35% in the primary specimen to 10% in the bone metastases suggesting a phenotypic change during progression to the bones [Badalian et al 2007].…”
Section: Trial Limitationsmentioning
confidence: 99%